2001
DOI: 10.1038/sj.gt.3301568
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirus-mediated transfer of prothymosin gene inhibits tumor growth and prolongs survival in murine bladder cancer

Abstract: To explore the potential use of prothymosin α(ProT) ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…‫,ء‬ p Ͻ 0.05; ‫,ءء‬ p Ͻ 0.01. of synovial fibroblasts. This result is in agreement with our earlier reports showing the abrogation of growth-promoting activity of ProT by deleting its NLS (27). In the rat CIA model, NLS-deleted ProT gene transfer ameliorated the clinical course of CIA.…”
Section: Figuresupporting
confidence: 93%
See 3 more Smart Citations
“…‫,ء‬ p Ͻ 0.05; ‫,ءء‬ p Ͻ 0.01. of synovial fibroblasts. This result is in agreement with our earlier reports showing the abrogation of growth-promoting activity of ProT by deleting its NLS (27). In the rat CIA model, NLS-deleted ProT gene transfer ameliorated the clinical course of CIA.…”
Section: Figuresupporting
confidence: 93%
“…We have shown previously that NIH3T3 cells overexpressing ProT increase the proliferative activity by shortening the duration of the G 1 phase (9). We have also reported that cell growth is enhanced in ProT gene-transduced mouse bladder cancer cells, and that such growth-promoting activity of ProT can be abolished if its NLS is deleted (27). In this study, we found that the lining layer of synovial tissue from patients with RA expressed ProT.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…We next produced an rAAV/ProT vector expressing ProT by using the PS virus system and tested its ability to mediate gene transfer. ProT, a putative thymic hormone, has been shown to exert antitumor effects on murine bladder cancer when delivered by retroviral vectors (32). Expression of the ProT protein was detected in rAAV/ProT-infected NIH 3T3 cells by immunohistochemistry at 72 h postinfection (Fig.…”
Section: Generation Of Recombinant Packaging-helper Prvmentioning
confidence: 95%